Pollen, People and Place: Multidisciplinary Perspectives on Ecosystem Change at Amboseli, Kenya - Githumbi, Esther N.; Kariuki, Rebecca; Shoemaker, Anna; Courtney-Mustaphi, Colin J.; Chuhilla, Maxmillian; Richer, Suzi; Lane, Paul; Marchant, Rob (Frontiers in Earth Science, 2018)
This study presents a multidisciplinary perspective for understanding environmental change and emerging socio-ecological interactions across the Amboseli region of southwestern Kenya. We focus on late Holocene (<5000 cal yr. BP) changes and continuities reconstructed from sedimentary, archaeological, historical records and socio-ecological models. We utilize multi-disciplinary approaches to understand environmental-ecosystem-social interactions over the longue durée and use this to simulate different land use scenarios supporting conservation and sustainable livelihoods using a socio-ecological model. Today the semi-arid Amboseli landscape supports a large livestock and wildlife population, sustained by a wide variety of plants and extensive rangelands regulated by seasonal rainfall and human activity. Our data provide insight into how large-scale and long-term interactions of climate, people, livestock, wildlife and external connections have shaped the ecosystems across the Amboseli landscape. Environmental conditions were dry between ~5000–2000 cal yr. BP, followed by two wet periods at ~2100–1500 and 1400–800 cal yr. BP with short dry periods; the most recent centuries were characterised by variable climate with alternative dry and wet phases with high spatial heterogeneity. Most evident in palaeo and historical records is the changing woody to grass cover ratio, driven by changes in climate and fire regimes entwined with fluctuating elephant, cattle and wild ungulate populations moderated by human activity, including elephant ivory trade intensification. Archaeological perspectives on the occupation of different groups (hunter-gatherers, pastoralists and farmers) in Amboseli region and the relationships between them are discussed. An overview of the known history of humans and elephants, expanding networks of trade, and the arrival and integration of metallurgy, livestock and domesticated crops in the wider region is provided. In recent decades, increased runoff and flooding have resulted in the expansion of wetlands and a reduction of woody vegetation, compounding problems created by increased enclosure and privatisation of these landscapes. However, most of the wetlands outside of the protected area are drying up because of the intensified water extraction by the communities surrounding the National Park and on the adjacent mountains areas, who have increased in numbers, become sedentary and diversified land use around the wetlands.